Efectos del tratamiento con glucocorticoides durante el embarazo. A propósito de un caso - Diana Machado Ramírez (Revista Finlay)
The use of anti-inflammatory glucocorticoids may be necessary during pregnancy to treat some maternal conditions. Its effects in pregnant women are virtually the same as those described in the general adult population. Avascular necrosis is the death of bone tissue due to the interruption of the blood supply, and is mainly associated with the use of high-dose corticosteroids for long periods. We present the case of a 21-year-old patient at 34 weeks’ gestation admitted to the Intensive Care Unit of the Enrique Cabrera Hospital because of decompensated hypertension, obesity and congenital adrenal hyperplasia treated with suppressive doses of steroids. Subsequently, she was diagnosed with an avascular necrosis of both femoral heads. Iatrogenic Cushing’s syndrome resulting from all these factors was found. The newborn developed a seborrheic dermatitis of the scalp. The purpose of this presentation is to describe the side effects of the chronic use of glucocorticoids in pregnant women.